Epidemiological Profile of Users of a Psychosocial Care Center II in Northern Brazil (Research, Society and Development, 2022)
Mental disorders represent a serious public health problem, affecting people of all ages and both sexes. The aim of this study was to identify the prevalence of mental disorders and characterize the sociodemographic profile of users of the Psychosocial Care Center II Regional in Ji-Paraná, Rondônia. Data were collected from 6,207 medical records of users active in the service. As determined by the Resolution no. 466/2012, the research project was sent to the Ethics and Research Committee of the Centro Universitário São Lucas Ji-Paraná - RO, having been approved under the CAAE no. 29517319.9.0000.5297. Data analysis was performed through descriptive statistics, using relative and absolute frequencies, with a 95% confidence interval. The results demonstrated that 59.32% of the sample are female users, 39% are between 30 and 49 years old, 41% are single and 34.98% have incomplete elementary school. The most prevalent mental disorders were mood (affective), neurotic disorders, stress-related and somatoform disorders, schizophrenia, schizotypical and delusional disorders, in addition to mental and behavioral disorders due to the use of psychoactive substances. It is concluded that the results are aligned with the literature, regarding the age group, sex, marital status, and most prevalent disorders.